CD73 acts as a prognostic biomarker and promotes progression and immune escape in pancreatic cancer. Issue 15 (9th July 2020) - Chen, Qiangda; Pu, Ning; Yin, Hanlin; Zhang, Jicheng; Zhao, Guochao; Lou, Wenhui; Wu, Wenchuan
Abstract: CD73 is a glycosylphosphatidylinositol (GPI)‐anchored protein that attenuates tumour immunity via cooperating with CD39 to generate immunosuppressive adenosine. Therefore, CD73 blockade has been incorporated into clinical trials for cancers based on preclinical efficacy. However, the biological role and underlying mechanism of CD73 in pancreatic cancer (PC) microenvironment and its prognostic impact have not been comprehensively studied. In this article, we found that the expression of CD73 was up‐regulated in PC tissues and patients with higher CD73 expression had poorer overall survival (OS) and disease‐free survival (DFS) in multiple publicly available databases. Higher CD73 expression was significantly associated with its reduced methylation, and only the hypomethylation of CpG site at cg23172664 was obviously correlated with poorer OS. Then, Metascape analysis and GSEA showed that CD73 may play an important role in PC progression and immune regulations. Notably, CD73 was verified to be negatively correlated with infiltrating levels of CD8 + T cells and γδ + T cells in both TCGA and GEO cohorts via the CIBERSORT algorithm. In addition, patients with higher CD73 expression also tended to have higher PD‐L1 expression and tumour mutation load. It seemed that CD73 might be a promising biomarker for the response to the anti‐PD‐1/PD‐L1 treatment in PC. In conclusion, these results reveal that CD73 may function as a promotor in cancer progression and a regulator in immune patterns via CD73‐related pathways. Blockade of CD73 might be a promising therapeutic strategy for PC.